Why Empathy is not the Best Basis for Humanitarianism - Fritz Breithaupt (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2015)
The paper challenges the assumption that empathy is the key source of humanitarianism. It begins by asking what underlies the perception of empathy as one of the chief motors of humanitarian aid. This leads to an examination of the `scene of empathy'—which in turn sheds light on some of the more problematic aspects of empathy. Three of these problematic aspects and their importance for humanitarian aid are discussed, namely (temporary) self-loss, a tendency to radicalize conflicts and the danger of sadism. In conclusion, the author asks in how far humanitarianism can be decoupled from empathy and proposes an alternative approach. This alternative approach revolves around the development of a common we-identity which does not depend on empathy.
urn:nbn:de:hbz:464-20160127-142729-6
Keywords: 320; Humanitarianism; empathy; narrative; self-loss; conflict; sadism; we-identity